Hands-on explainable AI (XAI) with Python : interpret, visualize, explain, and integrate reliable AI for fair, secure, and trustworthy AI apps /: interpret, visualize, explain, and integrate reliable AI for fair, secure, and trustworthy AI apps. (2020) - Rothman, Denis
No abstract available